Pre-exposure prophylaxis as prevention strategy in the HIV transmission: characterization of the user - Alves Ferreira, Marlene; Cristina Rodrigues da Silva, Nádia; de Paula, Ludmila; Andrade, Heuler Souza (Revista Prevenção de Infecção e Saúde, 2022)
Introduction: The combined HIV prevention is the current strategy of prevention employed in coping with this disease. It makes combined use of biomedical, behavioral and structural interventions, applied at the level of individuals. This study aimed to characterize the user of PrEP of a hospital of Minas Gerais and his relationship with this proposal. Outline: Descriptive study based on secondary data, with a quantitative approach, carried out in 2020. To obtain the data, information available by the service itself, in the prophylactic care of users, was used. Results: Of the 80 users analyzed, 41.3% were between 22 and 30 years old, 86.3% were single and 80% considered themselves homosexuals, 37.5% claimed to have had a relationship with HIV+ people without using condoms, 100% of users underwent rapid testing for HIV. Implications: The findings demonstrate that PrEP has significantly contributed to HIV prevention. However, given the risk behavior of many users, there is a need for managers and health professionals to improve this intervention.